2014
DOI: 10.1128/mcb.01674-13
|View full text |Cite
|
Sign up to set email alerts
|

SRSF10 Regulates Alternative Splicing and Is Required for Adipocyte Differentiation

Abstract: bDuring adipocyte differentiation, significant alternative splicing changes occur in association with the adipogenic process. However, little is known about roles played by splicing factors in this process. We observed that mice deficient for the splicing factor SRSF10 exhibit severely impaired development of subcutaneous white adipose tissue (WAT) as a result of defects in adipogenic differentiation. To identify splicing events responsible for this, transcriptome sequencing (RNA-seq) analysis was performed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 28 publications
2
56
0
Order By: Relevance
“…Specific to adipogenesis, differential promoter usage and alternative splicing are required for the expression of the canonical adipogenic transcription factor Ppar␥ (26 -28, 43). Other regulatory factors are also formed from alternative splicing, including nCOR1 and Lipin1 (33,43,44). In the present study, we identified distinct roles of each splicing factor in generating Pparg mRNA splice variants.…”
Section: Determining Adipogenic Factors In the 14-3-3 Interactomementioning
confidence: 50%
See 1 more Smart Citation
“…Specific to adipogenesis, differential promoter usage and alternative splicing are required for the expression of the canonical adipogenic transcription factor Ppar␥ (26 -28, 43). Other regulatory factors are also formed from alternative splicing, including nCOR1 and Lipin1 (33,43,44). In the present study, we identified distinct roles of each splicing factor in generating Pparg mRNA splice variants.…”
Section: Determining Adipogenic Factors In the 14-3-3 Interactomementioning
confidence: 50%
“…The spliceosome is responsible for constitutive and alternative splicing of mRNA, whereby intronic regions of mRNA are removed or sections of mRNA enriched with splicing factors at regulatory elements are removed, respectively (24). Various splicing factors have been found to be important for adipogenesis (33,34), but no studies have directly tested the role of the spliceosome in this process. To this end, we found that inhibition of the spliceosome with madrasin was sufficient to block 3T3-L1 adipogenesis and prevent the generation of various Pparg splice variants.…”
Section: Determining Adipogenic Factors In the 14-3-3 Interactomementioning
confidence: 99%
“…However, cross-linking immunoprecipitation-sequencing (CLiP-seq) data in HEK293 cells (Sanford et al, 2009) revealed a binding site for SRSF1 (alias ASF/SF2) in exon 6 of PPARG ( Figure S3A). Therefore, according to the models proposed for the exclusion of exon 11 in MST1R gene (alias RON) mediated by SRSF1 (Ghigna et al, 2005) and exon 7 in Lipin1a mediated by SRSF10 (Li et al, 2014), the binding of SRSF1 to PPARG exon 6 might contribute to exon 5 exclusion. RNA immunoprecipitation (RIP) in control HEK293 cells, as well as in cells overexpressing SRSF1, confirmed that this splicing factor binds to PPARG pre-mRNA and mature transcripts ( Figures 1D and S3B).…”
Section: Pparg Activation Increases Exon 5 Skipping With the Contribumentioning
confidence: 99%
“…Specific to adipogenesis, differential promoter usage and alternative splicing are required for the expression of the canonical adipogenic transcription factor Pparγ (51)(52)(53). Other regulatory factors are also formed from alternative splicing, including nCOR1 and Lipin1 (54,55). Future studies are required to determine whether 14-3-3ζ directly binds to these splicing factors and how it regulates their splicing activity to generate essential adipogenic factors.…”
Section: Discussionmentioning
confidence: 99%